Alcohol Seeking Under Risk of Punishment Is Associated With Activation of Cortical and Subcortical Brain Regions - McDonald, Allison J.; Alonso-Lozares, Isis; Rauh, Vasco; van Mourik, Yvar; Schetters, Dustin; De Vries, Taco J.; Marchant, Nathan J. (Frontiers in Behavioral Neuroscience, 2021)
In humans, stimuli associated with alcohol availability can provoke relapse during abstinence. In this study, we investigated the role of discriminative stimuli (DS) in the control of alcohol seeking in two types of behavioral tests. The first test examined the ability of an alcohol-associated DS to promote alcohol seeking (relapse) after punishment-imposed abstinence in the presence of a different DS. Following this, we tested whether the differentially associated DS can promote and suppress alcohol self-administration in a within-session discrimination task. During the within-session discrimination task, we also tested the rate of alcohol self-administration when two DS are presented in a compound. We first trained Long-Evans male rats (n = 24) to self-administer alcohol in the presence of one DS (reward-associated discriminative stimulus, rewDS) and then punished that behavior in the presence of a different DS (punishment-associated discriminative stimulus, punDS). On the test, we found that rats tested with the rewDS showed higher alcohol seeking than rats tested with the punDS. This result shows that a single Cue DS can promote alcohol seeking in a manner comparable to contexts. Subsequently, we trained 16 of these rats in a within-session trial-based discrimination task, comprised of intervening 2-min trials of rewDS, punDS, or conflict with rewDS and punDS in compound and a reduced probability of punishment. We found that alcohol self-administration is bi-directionally regulated by the rewDS and punDS. In conflict trials, alcohol self-administration was at a rate that was intermediate between the rewDS and punDS trials. In a final test, rats were presented with one of the three trial conditions and perfused for Fos immunohistochemistry. We found Fos expression was higher in the rats tested in the conflict condition in three interconnected sub-cortical brain regions. This study demonstrated the important role that alcohol-associated DS plays an important role in promoting relapse to alcohol seeking after punishment-imposed abstinence. We also implemented a within-session discrimination task that allows for the study of alcohol seeking under motivational conflict, which may be relevant for alcohol use despite negative consequences. The results from the Fos data suggest that higher alcohol seeking in approach-avoidance motivational conflict is associated with activation of sub-cortical regions but not cortical regions.